Vocational School Students' Perceptions of the Use of Animated Movies in Narrative Text Learning - Syamsul Huda, Faishol Khoir; Rismiyanto, Rismiyanto; Kurniati, Diah (Journal of Education, Language Innovation, and Applied Linguistics, 2023)
This study aims to explore the perception of vocational school students in learning narrative texts by using animated movies. This study is qualitative research with the questionnaire and interview as the instruments of collecting data. The participants of this study were 36 students of a state vocational school in Pati regency, Indonesia majoring in the Financial & Institutional Accounting Program. The results of the questionnaire show that in general, 81.57% of the participants have a positive perception of the use of animated movies in learning narrative texts. Meanwhile, 18.43% of the participants have a negative perception. The results of interviews conducted with five students also reveal that most of the students agree on the use of animated movies because they help and support the learning process and are very easy to understand. From this research on the use of animated movies, teachers are suggested to use this media in teaching narrative texts. Keywords: Perception; Narrative Texts; Animated Movie.